Status social subjetivo, autoavaliação de saúde e tabagismo: estudo longitudinal de saúde do adulto (ELSA-Brasil) - Lidyane do Valle Camelo (2012)
INTRODUCTION: Health inequities do not result exclusively from absolute income levels, education or type of occupation, but also from individuals relative position in social hierarchy. The subjective social status expresses individuals sense of their relative place in social hierarchy. The object is to apprehend a dimension of social stratification which is not captured by ordinary objective indicators of social position, such as income and education. OBJECTS: To investigate if subjective social status is associated with self-rated health and tobacco smoking, independently of objective indicators of social position, among civil servants participating in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Additionally, we assess if there are differences in the magnitudes of theses associations, comparing three different reference groups for the subjective social status: other people from the society in general, other people from the local community and other people from the same work place. METHODOLOGY: Were legible for the study all the 15,105 civil servants between the age of 35 and 74 years who participated in the baseline of ELSA-Brasil (20082010). ELSA-Brasil is a prospective multicenter study developed in higher education and research institutions in six Brazilian states: Minas Gerais, São Paulo, Rio de Janeiro, Espirito Santo, Bahia e Rio Grande do Sul. All the participants were submitted to face-to-face interviews. The response variables were self-rated health (good/poor) and tobacco smoking (nonsmokers/former smokers/smokers). The main explanatory variable was the subjective social status measured by the two MacArthur Scales of Subjective Social Status, which use society and community as reference groups. A third scale was adapted for ELSA-Brasil, using the work environment as reference group. The adjustment variables were sex, age, skin color, education and net household income. Odds ratios (OR) and a 95% confidence interval were obtained by logistic regression for self-rated health, and multinomial regression for smoking. RESULTS: The correlations among SSS ladders were stronger than the association of these ladders with income and education. The prevalence of poor self-rated health was of 19.9%; of former smoking, 30%; and of current smoking, 13.1%. In all three scales, the lower the subjective social status, the higher the prevalence of poor self-rated health. Current and former smoking were also associated with low subjective social status in the three scales, but there was no gradient for former smoking. Independently of objective measures of social position, low subjective social status was significantly associated with poor self-rated health and former smoking, although not with current smoking. No significant differences were identified between the magnitudes of these associations in the three scales. CONCLUSION: The results suggest that subjective social status, education and income represent distinct aspects of social inequalities and indicate that the impact of these variables on health or health-related behavior is different. This reinforces the importance of subjective social status as a complementary measure in the study of social inequities in health and contributes to the increase of researches which highlight the importance of perception of social status to health.